Does Timing of Implant Placement Affect Implant Therapy Outcome in the Aesthetic Zone? A Clinical, Radiological, Aesthetic, and Patient‐Based Evaluation. (20th February 2014) - Hof, Markus; Pommer, Bernhard; Ambros, Harald; Jesch, Philip; Vogl, Susanne; Zechner, Werner
Abstract: Purpose: To compare five different implant treatment protocols in the anterior maxilla, including immediate, early, and delayed implant placement, as well as implant placement in conjunction with simultaneous guided bone regeneration and implant placement 3 months following horizontal autologous bone block grafting. Material and Methods: Aesthetic indices used included the Pink Esthetic Score (PES), Papilla Index (PI), Subjective Esthetic Score (SES), and White Esthetic Score (WES). Subjective evaluation of implant aesthetics was performed using a visual analogue scale (VAS). The VAS consisted of a 10 cm–long line representing the degree of discontent (0%) or satisfaction (100%). Results: A total of 153 implants in 153 patients (80 women, 73 men) were evaluated after a mean follow‐up of 4.5 ± 2.9 years. Mean peri‐implant bone loss was 1.6 ± 0.9 mm and not affected by treatment protocol, time after implant placement, or crown length. Papilla presence, by contrast, differed significantly between the protocols: Papilla formation was more pronounced following delayed and immediate implant placement. No statistical significance was found among treatment modalities with regard to PES, SES, or WES. Longer crowns were associated with lower PES and PI ratings and correlated with greater midfacial recession. SES was also influenced by time after implant placement and keratinized mucosa. Patient satisfaction differed significantly among treatment protocols, favoring immediate implant placement. Agreement between objective and subjective aesthetic ratings was low. Conclusion: The present study suggests that comparable clinical, radiological, and aesthetic results can be achieved with all treatment protocols. Gingival recession, however, seems to occur in the long term irrespective of the technique used.